THE QUANTITATIVE LEPROMIN TEST IN LEPROSY - PRIETO ROSAS, L; MALLEN SALAZAR, M (Instituto Nacional de Cardiología, CD MEXICO, DF, MEX, 1946)
The silver staining technique of Rio-Hortega was used to study the neuroglia cells of the pineal gland of various spp Independent of the parenchymatous structure, the pineal gland possesses a true neurologic framework increasing in complexity with age
ANN ALLERGY
Keywords: QUANTITATIVE, LEPROMIN, TEST, LEPROSY; CIENCIAS MEDICAS; CIENCIAS CLINICAS; PATOLOGIA CLINICA